Pelatihan Manajemen Keuangan pada Usaha Mikro Kecil (UMK) Taman Wisata Bumi Semendung Kota Madiun - Srimulyani, Veronika Agustini; Handayani, Wahyu Prabawati Putri; Waloyo, Lorensius Anang Setiyo (Jurnal Dharma Bhakti Ekuitas, 2023)
Micro and small businesses have an important role in economic growth in Indonesia, and to find out the performance of the development of micro and small businesses can be seen from the financial reports of the businesses they run. The skills of business actors in good financial management, especially business financial records, are one of the obstacles in the development of micro and small businesses in Indonesia. The Madiun City Government is very concerned about the growth and development of micro and small businesses, by developing stalls in every sub-district in Madiun City. Service partners are one of the stalls that caught the team's attention, namely a shop located in the Bumi Semendung tourist park area, because it is quite attractive to the people of Madiun and its surroundings, as a culinary tourism destination. The service program carried out by this team is training in calculating cost of goods sold and making simple financial reports. Additional training in the form of practical use of Android-based digital applications for recording sales transactions. Programs are determined based on team and partner agreements. The training participants were 12 micro and small business owners selling in Bumi Semendung, and as many as 10 people have not calculated product selling prices and recorded financial reports. By implementing this service program, all training participants gain additional new insights and skills. Training participants gain additional new insights on how to determine product selling prices, prepare financial reports according to MSME financial accounting standards, and practice one of the financial activities, namely recording sales transactions using digital applications via their respective smartphones. The next micro and small business service program at the Bumi Semendung tourist park is digital marketing training, with the aim of improving the quality of micro and small business management. Keywords: Cost of Goods Sold, Financial Statements, Sales Transactions. Abstrak Usaha mikro kecil memiliki peranan penting dalam pertumbuhan ekonomi di Indonesia, dan untuk mengetahui kinerja perkembangan usaha mikro kecil dapat dilihat dari laporan keuangan usaha yang dijalankan. Keterampilan pelaku usaha dalam pengelolaan keuangan yang baik, khususnya pencatatan keuangan usaha, menjadi salah satu kendala dalam pengembangan usaha mikro dan kecil di Indonesia. Pemerintah Kota Madiun sangat memperhatikan tumbuh kembang usaha mikro dan kecil, dengan mengembangkan warung di setiap kecamatan yang ada di Kota Madiun. Mitra jasa merupakan salah satu lapak yang menarik perhatian tim yaitu warung yang berada di kawasan taman wisata Bumi Semendung, karena cukup diminati oleh masyarakat Madiun dan sekitarnya, sebagai tujuan wisata kuliner. Program pengabdian yang dilakukan tim ini adalah pelatihan menghitung harga pokok penjualan dan membuat laporan keuangan sederhana. Pelatihan tambahan berupa praktik penggunaan aplikasi digital berbasis Android untuk pencatatan transaksi penjualan. Program ditentukan berdasarkan kesepakatan tim dan mitra. Peserta pelatihan adalah 12 orang pemilik usaha mikro dan kecil yang berjualan di Bumi Semendung, dan sebanyak 10 orang belum melakukan perhitungan harga jual produk dan pencatatan laporan keuangan. Dengan pelaksanaan program pengabdian tersebut, semua peserta pelatihan mendapatkan tambahan wawasan baru dan ketrampilan dalam menentukan harga jual produk, menyusun laporan keuangan sesuai standar akuntansi keuangan UMKM, dan mempraktekkan salah satu kegiatan keuangan yaitu pencatatan transaksi penjualan menggunakan aplikasi digital melalui smartphone masing-masing. Program pengabdian usaha mikro dan kecil selanjutnya di taman wisata Bumi Semendung adalah pelatihan pemasaran digital, dengan tujuan untuk meningkatkan kualitas pengelolaan usaha mikro dan kecil. Kata kunci: Harga Pokok Penjualan, Laporan Keuangan, Transaksi Penjualan.